Natural gas conversion IV : proceedings of the 4th International Natural Gas Conversion Symposium, Kruger Park, South Africa, November 19-23, 1995 - International Natural Gas Conversion Symposium 1995 : Kruger National Park, South Africa); De Pontes, M.; ScienceDirect eBooks (Amsterdam ; New York : Elsevier, 1997)
The Fourth International Natural Gas Conversion Symposium was attended by 180 delegates from 25 countries. Representation was evenly balanced between industry and academia. The opening address was delivered by Mr Roy Pithey, Chairman of South Africa's Central Energy Fund, who dealt with the importance and utilisation of natural gas in sub-Saharan Africa. Plenary lectures were presented by Professors E. Iglesia (Catalyst design and selectivity for F-T synthesis) and E.E. Wolf (Oxidative Coupling Methane). A number of keynote addresses were delivered: - Dr T. Fleisch (Amoco) described the use of DME as a transport fuel and the work which has been carried out in this area in collaboration with Haldor Topsoe - Professor L.D. Schmidt (Univ. of Minnesota) explained his work on the direct conversion of methane at high velocities - Dr B. Jager (SASTECH R & D) reported on the recent developments in slurry and fluidized bed F-T reactors as SASOL - Dr J. Rostrup-Nielsen (Haldor Topsoe) discussed the role of catalysis in the conversion of natural gas for power generation. Areas signalled for further research were: direct conversion of methane to intermediate monomers; methanol conversion to higher alcohols; CO/H2 conversion in a commercially viable route to higher alcohols; and CO/H2 conversion to high quality gasoline. It is obvious that such developments would fit into the energy cycle which has moved from wood, to coal, to oil, to gas, and will most probably move to hydrogen.
Front Cover; NATURAL GAS CONVERSION IV; Copyright Page; Table of Contents; Preface; Organising and Advisory Committee; Financial Support; PART 1: SYNTHESIS OF ALCOHOLS AND OTHER OXYGENATES; PART 2: ECONOMICS AND INDUSTRIAL PROCESSES; PART 3: FISCHER-TROPSCH; PART 4: NOVEL METHANE REACTIONS; PART 5: OXIDATIVE COUPLING; PART 6: PARTIAL OXIDATION; PART 7: REFORMING; AUTHOR INDEX; OTHER VOLUMES IN THE SERIES.
Includes bibliographical references and index.
Print version record.
Elsevier
Keywords: Synthetic fuels -- Congresses; Natural gas -- Congresses; TECHNOLOGY & ENGINEERING -- Chemical & Biochemical; Natural gas; Synthetic fuels; Aardgas; Alcoholen; Synthese (chemie); Conversie; Fischer Tropsch synthese; Oxidative coupling; Katalyse; Electronic books